Greening of doctoral training and research practices - Guzmán Ibarra, Isabel (IE Revista de Investigación Educativa de la REDIECH, 2021)
The current planetary crisis generates unsustainable levels of environmental and human degradation. This calls for a reform of thought that goes beyond disciplinary visions to face complex reality. This article communicates an experience of research-teaching religation that looked for alternative ways to establish the dialogue of knowledge and the greening of training and doctoral research practices. The research-action-training-experience method was used, through self-socio-ecoformation strategies that enhance in students’ ways of relating to themselves, with others and with the world; these involvement processes are described in a student-case study. The partial results show a greening of training-research as a recursive and creative process of knowledge to understand reality. As conclusions, it is shown that the scaffolding that has been laid gives an account of the pilgrimage of the doctoral students who venture to generate a feeling-thinking-acting as the articulating axis of their transformation into a walk that begins in the self, to interweave with others, and thinking to the world.